2017
DOI: 10.1093/annonc/mdw686
|View full text |Cite
|
Sign up to set email alerts
|

Complex chromosomal rearrangements by single catastrophic pathogenesis in NUT midline carcinoma

Abstract: BackgroundNuclear protein in testis (NUT) midline carcinoma (NMC) is a rare aggressive malignancy often occurring in the tissues of midline anatomical structures. Except for the pathognomonic BRD3/4–NUT rearrangement, the comprehensive landscape of genomic alterations in NMCs has been unexplored.Patients and methodsWe investigated three NMC cases, including two newly diagnosed NMC patients in Seoul National University Hospital, and a previously reported cell line (Ty-82). Whole-genome and transcriptome sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 22 publications
5
59
0
Order By: Relevance
“…The NUT gene translocation pattern was simple in the FISH assay in all cases except NC13, which showed NUT gene gains with an isolated red signal in addition to paired green and red signals. Consistently, it was previously reported that chromosomal alterations underlying the simple BRD4 / BRD3 ‐ NUT transcript can be highly sophisticated and even harbor hyperdiploidy .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The NUT gene translocation pattern was simple in the FISH assay in all cases except NC13, which showed NUT gene gains with an isolated red signal in addition to paired green and red signals. Consistently, it was previously reported that chromosomal alterations underlying the simple BRD4 / BRD3 ‐ NUT transcript can be highly sophisticated and even harbor hyperdiploidy .…”
Section: Discussionsupporting
confidence: 81%
“…We observed high and frequent overexpression of p53 in NUT carcinoma cases. The reason for this finding is uncertain because chromosomal rearrangement or somatic mutation of p53 was not found in the SNU‐2972‐1 or SNU‐317S cell line in our previous study . p300 HAT is sequestered to the NUT moiety BRD4‐NUT, which, in turn, acetylates p53 and binds it to the BRD4‐NUT foci of the chromatin .…”
Section: Discussionmentioning
confidence: 78%
“…The extensive work done by this group in Korea indicates that the reciprocal translocation involving NUTM1 results from complex multiple chromosomal rearrangements, termed chromoplexy, that ultimately give rise to a single reciprocal translocation and the simple t(15;19) karyotype. The majority of mutations in three early passage NC cell lines tested in the study had a clock‐like molecular signature, consistent with those predicted from a tumor that arises from a normal somatic cell . The findings suggest that NC may arise from a single catastrophic chromosomal event in an otherwise healthy dividing cell.…”
Section: Cytogeneticssupporting
confidence: 73%
“…While it is not unusual for an NC patient to have a smoking history, there is no evidence that smoking or any other etiology (environmental or viral) is associated with NC. Nevertheless, due to small numbers of patients, no epidemiologic study has been conducted that has rigorously analyzed etiologic factors, thus the current thought, which is supported by NGS data, is that the BRD4‐NUTM1 translocation occurs within a somatic cell as a single catastrophic event due to chance alone …”
Section: Demographics and Prevalencementioning
confidence: 99%
“…The breakpoint in NUTM1 was upstream of exon 1 and not exon 2. Exon 1 breakpoints have been reported and are quite frequent . Unlike exon 2, exon 1 lacks a splice acceptor site and hence is not included in the transcript.…”
mentioning
confidence: 99%